The Role of Vitamin D in Parkinson's Disease - Fatma Öznur Afacan; Didem Önay Derin (International Journal of Gastronomy Research)
Parkinson's disease (PD) is a progressive neurodegenerative disorder marked by tremor, rigidity, bradykinesia, and postural instability, along with non-motor symptoms that can cause disability. Vitamin D, a fat-soluble secosteroid, influences gene expression by binding to the vitamin D receptor (VDR). It is essential for calcium homeostasis and metabolism and is also linked to various health conditions, including PD. In recent years, a high prevalence of vitamin D deficiency has been observed in PD patients. The enzymes converting vitamin D to its active form, VDR, and 1α-hydroxylase, are highly expressed in the substantia nigra. These findings indicate that low vitamin D levels may cause dysfunction or cell death in this brain region. Vitamin D impacts several biological processes in the central nervous system, including neurotransmission in dopaminergic circuits. Studies show lower vitamin D levels in Parkinson's patients compared to healthy controls. Links have been found between vitamin D levels and non-motor symptoms like mood disorders, orthostatic hypotension, and olfactory dysfunction, as well as motor severity. However, information on vitamin D's effects on non-motor symptoms is limited. This review seeks to critically examine the relationship between vitamin D and PD, focusing on the potential mechanisms through which vitamin D may influence the development, progression, and clinical management of PD. Additionally, it aims to evaluate the role of vitamin D in the prevention of PD and its therapeutic potential as an adjunctive treatment in patients with Parkinson’s disease.